The efficacy of powered toothbrushes following a brushing exercise: a systematic review. Issue 1 (25th December 2014) - Rosema, NAM; Slot, DE; van Palenstein Helderman, WH; Wiggelinkhuizen, L; Van der Weijden, GA
Abstract: Aim: The primary objective was to determine, based on the available published evidence, the efficacy of powered toothbrushing following a brushing exercise and secondary to what magnitude this effect is dependent on the plaque index score, power supply and mode of action. Material and Methods: The PubMed–MEDLINE and Cochrane CENTRAL databases were searched through and up to August 2014 to identify appropriate studies. The outcome measurement was the weighted mean (WM) percentage plaque score reduction of a full‐mouth assessment following subject brushing. Results: The search yielded 2420 titles and abstracts. Ultimately, 58 articles with 146 brushing exercises as separate legs were selected. The overall effect of a powered brushing exercise provides a 46% WM plaque score reduction. One hundred and six experiments provided data as assessed according to the Quigley and Hein plaque index. The WM reduction from baseline in plaque scores was 36%. A WM plaque score reduction of 65% was observed in 39 experiments using the Navy plaque index. Subanalysis on power supply and mode of action showed WM plaque score reductions ranging from 33% up to 71% depending on plaque index score. Conclusion: The efficacy in plaque removal following a brushing exercise using a powered toothbrush provides a WM plaque score reduction of 46% on average, with a range of 36–65% dependent on the index scale to score plaque. The available evidence indicates that the power supply (rechargeable or replaceable battery), mode of action, as well as brushing duration and type of instructions are factors which contribute to the variation in the observed efficacy.